Caracterización fisicoquímica de Miel de Abeja (Apis Mellifera) de tres distritos de la provincia de Sánchez Carrión - Coronel Peña, Juan Rafael (2017)
At present, the tendency to consume healthy foods is increasing, and mixtures with natural products with high protein value and without the use of additives are demanded by the consumer. The objective of the present study was to physicochemically characterize honey of bee (Apis mellifera) of three districts of the province of Sánchez Carrión; being these physicochemical characteristics,% humidity,% total solids, specific weight, pH, acidity,% ash and finally the electrical conductivity. To compare the samples among each other, an analysis of variance was performed for each parameter, which allowed to compare means between the different samples of honey, when this analysis was significant, the respective groups of measurements were formed by Tukey's multiple comparisons test. a confidence level of 95% helped by statistical software Statgraphics Centurion version 16.1. In this study we obtained results of% humidity of 24.76%, 20.9% and 24.3%, where samples M1 and M3 exceed the range specified by NTP 209.168-1999; In addition, it was observed values of 75.23%, 79.1% and 75.66% the determination of% of total solids demonstrating its high purity M2 rejecting its adulteration as possibly M1 and M3 if they could have been. Regarding the specific weight, values were obtained within the range of 1.4 to 1.6 cm3 / g, and no significant differences were found in values of 1426, 1.43 and 1423 cm3 / g. Refractive indices of 1.4745, 1.48423, 1.4756 were determined, the base parameter for the determination of% moisture, which indicates that the optimum value is found in M2 since values of M1 and M3 have values that are outside the permissible values. Additionally, a% ash was obtained, with values of 0.21%, 0.24% and 0.25% all within the allowable range as well as pH values of 3,723, 3,533 and 3,826. Likewise,% acidity of 30,367, 30,233 and 30,133 and an electrical conductivity of 32,333, 41,033 and 34,367 μS / cm was determined.